Analysis of the Judge's Decision on Sexual Crimes Against Children (Study of the Decision of the Purwokerto District Court Number: 16/Pid.Sus-Child/2022/PN Pwt) - A’maludin, Risqi (UM Purwokerto Press, 2023)
The main problem of this research is how the legal considerations of judges in imposing verdicts on sexual crimes committed by children. The main problem is further elaborated in several sub-problems or research questions, namely: 1) How is the consideration of the panel of judges in handing down a verdict on sexual crimes against children in criminal case Number. 16/Pid.Sus-Child/2022/PN Pwt? 2) Is the decision of the Makassar District Court judge in case no. 16/Pid.Sus-Anak/2022/PN Pwt is in accordance with the provisions of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System? The type of research used is Normative Legal Research. The data source of this research comes from secondary data. This research is classified as research with qualitative data types, namely by managing secondary data sourced from related laws. To find out whether the judge in giving a decision has carried out his duties in accordance with the authority given and fulfills a sense of justice for the community, victims, and perpetrators, a fundamental analysis is needed regarding the judge's decision on sexual violence against minors. Based on the background of the problem.